Determination of genomic regions associated with early storage root formation and bulking in cassava - Abah, Simon Peter; Mbe, Joseph Okpani; Dzidzienyo, Daniel Kwadjo; Njoku, Damian; Onyeka, Joseph; Danquah, Eric Yirenkyi; Offei, Samuel Kwane; Kulakow, Peter; Egesi, Chiedozie Ngozi (Frontiers in Plant Science, 2024)
Early cassava storage root formation and bulking is a medium of escape that farmers and processors tend to adopt in cases of abiotic and biotic stress like drought, flood and destruction by domestic animals. In this study, 220 cassava genotypes from International Institute for Tropical Agriculture (IITA), National Root Crops Research Institute (NRCRI), International Center for Tropical Agriculture (CIAT), Local (from farmer's field) and NextGen project were evaluated in three locations (Umudike, Benue and Ikenne). The trials were laid out using split plot in randomized incomplete block design (Alpha lattice) with two replications and in 2 years. The storage roots for each plant genotype were sampled or harvested at 3, 6, 9, and 12 MAP. All data collected were analyzed using R-statistical package. The result showed moderate to high heritability among the traits and there were significant differences (P<0.05) among the performances of the genotypes. The genome-wide association mapping using BLINK model detected 45 single nucleotide polymorphisms (SNPs) markers significantly associated with the four early storage root bulking and formation traits on chromosome 1, 2, 3, 4, 5, 6, 8, 9, 10, 13, 14, 17 and 18. 199 putative candidate genes were found to be directly linked to early storage root bulking and formation. The functions of these candidate genes were further characterized to regulate (i) phytohormonal biosynthesis, (ii) cellular growth and development (iii) biosynthesis of secondary metabolites for accumulation of starch and defense. Genome wide association study also revealed the presence of four pleiotropic SNPs, which control starch content, dry matter content, dry yield and bulking and formation index. The information on the GWAS could be used to develop improved cassava cultivars by breeders. Five genotypes (W940006, NR090146, TMS982123, TMS13F1060P0014 and NR010161) were selected as best early storage roots bulking and formation genotypes across the plant age. These selected cultivars should be used as sources of early storage root bulking and formation in future breeding programmes.